Drying kinetics and thermal energy evaluation of Moringa oleifera leaves drying using dehumidification with zeolite - Siqhny, Zulhaq Dahri; Sari, Anisa Rachma; Utari, Febiani Dwi; Djaeni, Mohamad (Journal of Bioresources and Environmental Sciences, 2024)
Moringa Oleifera leaves contain many phytochemical compounds, as the potential source of antioxidants. The leaves must be converted into dried form to extend the shelf life and prevent the nutritional qualities. The lack of a common sun-drying process for Moringa Oleifera leaves is dependent on the weather. But using convective dryers also requires high investment costs and results in very low energy efficiency. One potential option to enhance energy efficiency is lowering the humidity by dehumidification with zeolite. This research aims to evaluate the effect of drying temperature and the weight of adsorbent (zeolite) on drying kinetic and thermal efficiency of Moringa Oleifera leaves drying. Moringa Oleifera leaves were dried under different drying temperatures (30-70℃) and weight of zeolite (0-0.3 kg). The moisture content of Moringa Oleifera leaves and the input-output temperature was recorded to evaluate the moisture reduction and thermal efficiency. Results showed that the Page model can be used to predict the drying time. At the higher drying temperature and higher zeolite weight, moisture reduction and thermal efficiency increased. But the effect of zeolite is only significant in drying at temperatures below 50℃.